Simulation of biodiesel production through heterogeneously catalysed transesterification of vegetable oil by calcium ethoxide - Faseha, Jamali (2010)
Biodiesel is a clean burning alternative fuel, produced from domestic, renewable resources such as plant oils, animal fats, used cooking oil and even new sources such as algae. Biodiesel is also defined as fuel which has the same characteristics with commercial diesel in terms of its molecular formula. The transesterification reaction can be carried out using both homogeneous (acid or base) and heterogeneous (acid, base, or enzymatic) catalyst. Homogeneous catalysts provide much faster reaction rates than heterogeneous catalysts, but it is considerably more costly to separate homogenous catalysts from the reaction mixture (Liu et al., 2008). Therefore, heterogeneously base catalysts are studied in this research. The objective of this study is to find the feasibility of new type of heterogeneous catalyst in determining the best operating parameters and design factors which affecting the performance of biodiesel production. Aspen Plus 12.1 is used to performed the simulation study for feasibility of the biodiesel production using heterogeneous catalyst through a plug flow reactor (PFR). The simulation was done by incorporating the reaction kinetics and thermodynamics model into the reactor model. The NRTL of thermodynamics model is used in this research in order to perform the separation process for two liquid phases in the transesterification of vegetable oil process. The simulation was run after all the important property data had been incorporated into Aspen Plus simulator. After running all the operating parameters, it shows that the best temperature is 65 0C, the best molar ratio of methanol to oil is 6:1, the best mass ratio of catalyst to oil is 3% and the best space velocity is 0.25 hr-1 on oil conversion and biodiesel yield percentage. The PFR reactor schemes which are in single PFR, two PFR in series and PFR to CSTR were proposed as a suitable scheme for the production of biodiesel. Hence that, at the optimum operating condition, the conversion is 91.5%.